Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasi Pada Karyawan PT. Mega Finance Cabang Gorontalo - Sriwahyuni Ys Dengo; Syarwani Canon; Sudirman Sudirman; Rosman Ilato; Melizubaida Mahmud (Journal of Economic and Business Education, 2023)
It employed a quantitative method with a sample of 32 people. Moreover, the data collection technique used a questionnaire, while the data analysis technique was multiple linear regression analysis. The findings depicted that the variables of salary/income satisfaction, job satisfaction, and work environment partially and simultaneously had a positive and significant effect on employee organizational commitment at PT Mega Finance Cabang Gorontalo Branch. Moreover, this research obtained a coefficient of determination (R2) of 85,8% from variables of salary/earning satisfaction job satisfaction, and work environment on organizational commitment of employees at PT Mega Finance Cabang Gorontalo Branch. At the same time, the remaiping 14,2% was affected by other variables that were not explained in this research.